Epistemologi Sains Islam: Studi Ayat-Ayat Kauniyah dan Relevansinya dengan Ilmu Pengetahuan Modern dalam Konteks Global - Muhammad Nur Zakaria; Dimas Mochammad Fikri Islam; Dimas Makhzum Mufrih (Universitas Muhammadiyah Gresik, 2026)
The rapid advancement of modern science and technology has generated significant progress while simultaneously raising epistemological questions concerning the sources, orientation, and purpose of scientific knowledge. Islamic scientific epistemology offers an alternative paradigm that integrates divine revelation with scientific inquiry through the Qur'anic Kauniyah verses. However, previous studies have predominantly adopted a scientific concordism approach, focusing on demonstrating the compatibility between the Qur'an and modern scientific discoveries, while paying limited attention to the epistemological function of Kauniyah verses as the foundation for knowledge construction. This study aims to reconstruct the epistemology of Islamic science based on Kauniyah verses and to examine its relevance to the development of modern science in the global context. Employing a qualitative approach with a library research design, this study analyzes primary and secondary sources, including the Qur'an, scholarly books, and peer-reviewed journal articles on Islamic epistemology, philosophy of science, and the integration of science and religion. Data were analyzed through qualitative content analysis combined with comparative and conceptual approaches. The findings reveal that Kauniyah verses function as an epistemological foundation that integrates revelation, reason, empirical observation, and intuition into a coherent framework for knowledge production. This study proposes an integrative model of Islamic scientific epistemology in which revelation serves as the normative foundation, reason as the instrument of rational inquiry, empirical observation as the mechanism of scientific verification, and intuition as the means of ethical and spiritual reflection. Unlike the scientific concordism approach, the proposed framework positions Kauniyah verses as a conceptual basis for constructing scientific knowledge rather than merely validating scientific discoveries.